RAPIDLY PROGRESSIVE GLOMERULONEPHRITIS IN CHILDREN - Eva, Floria; Nilawati, Gusti Ayu Putu (Medicina, 2015)
Rapidly progressive glomerulonephritis (RPGN) is a rare syndrome in children and one of the nephrologyemergency which needs special attention. Rapidly progressive glomerulonephritis  is determined bysymptoms and signs of glomerulonephritis (GN); edema, hypertension, gross hematuria, and rapid lossof renal function. Early diagnosis and appropriate treatment play a critical role in saving renal functionand preventing permanent glomerular damage. Diagnosis was made based on clinical and laboratoryfindings. We reported two cases of RPGN in an eleven year old boy and an eight year old boy. The patientcame  to  the pediatric outpatient clinic at sanglah hospital with chief complaint dark  ?cola colored?urine. Laboratory work up showed proteinuria, erythrocyturia, decrease of C3 and normal C4 complementlevel, increased serum urea and creatinine level and loss of renal function in a few days with glomerularfiltration  rate  decreased. Based  on  clinical  and  laboratory  findings,  the  patient was  diagnosed  asrapidly progressive glomerulonephritis. The patient was given methylprednisolone pulses for 3 days,followed  by  high  dose  oral methylprednisolone. Prognosis  of  the  patient was  good.  [MEDICINA2015;46:46-51].